2019
DOI: 10.1021/acs.jproteome.9b00263
|View full text |Cite
|
Sign up to set email alerts
|

Deep Metabolomics of a High-Grade Serous Ovarian Cancer Triple-Knockout Mouse Model

Abstract: High-grade serous carcinoma (HGSC) is the most common and deadliest ovarian cancer (OC) type, accounting for 70-80% of OC deaths. This high mortality is largely due to late diagnosis. Early detection is thus crucial to reduce mortality, yet the tumor pathogenesis of HGSC remains poorly understood, making early detection exceedingly difficult. Faithfully and reliably representing the clinical nature of human HGSC, a recently developed triple-knockout (TKO) mouse model offers a unique opportunity to examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 101 publications
0
22
0
Order By: Relevance
“…Blood samples were spin down at room temperature for 5 min, 1000 rpm, then transfer the plasma into a new tube and stored at −80 • C [60] for UPLC-MS analysis.…”
Section: Plasma Samples Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood samples were spin down at room temperature for 5 min, 1000 rpm, then transfer the plasma into a new tube and stored at −80 • C [60] for UPLC-MS analysis.…”
Section: Plasma Samples Collectionmentioning
confidence: 99%
“…UPLC-MS analyses were performed at the Mass Spectrometry Core Facility at Georgia Institute of Technology according to previously described protocols [60].…”
Section: Uplc-ms Analysismentioning
confidence: 99%
“…7C), suggesting a presumed role of progesterone in immune suppression and inflammation (61,62). Additionally, as significant metabolome changes are evident during the development and progression of HGSC (63), progesterone may also elicit metabolomic alterations specific to HGSC development. Crucially, known as "BRCAness," tumors wild type for BRCA1/2 can harbor molecular features similar to those in tumors from BRCA-mutation carriers (42).…”
Section: ) (C-h)mentioning
confidence: 99%
“…development and progression in TKO model, our recent study has identified a panel of 29 serum metabolites that can distinguish early-stage HGSC from normal controls and also from advanced-stage HGSC with high accuracy, thus offering useful guidance on early detection of ovarian cancer [59].…”
Section: Plos Geneticsmentioning
confidence: 99%